A discovery of witches - Harkness, Deborah, 1965- (Harkness, Deborah E., 1965- All souls trilogy, 2011)
Witch and Yale historian Diana Bishop discovers an enchanted manuscript, attracting the attention of 1,500-year-old vampire Matthew Clairmont. The orphaned daughter of two powerful witches, Bishop prefers intellect, but relies on magic when her discovery of a palimpsest documenting the origin of supernatural species releases an assortment of undead who threaten, stalk, and harass her.